Absolute Competency Problems in Settlement of Mortgage Rights Execution Disputes of Islamic Banking in Religious Courts - Ricky Riyyano (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2020)
Banking activities, especially credit/financing transactions, apart from the existence of trust between creditors and debtors, also require guarantees that have a high liquidity value in the form of material guarantees and individual guarantees. The District Court does not have the authority to resolve sharia economic disputes in any form, including the execution of the object of mortgage rights in Islamic banking which has issued Constitutional Court Decision Number 93/PUU-X/2012. If the ruling or decision issued by the district court is related to implementation the object of mortgage rights in sharia banking, then the stipulation or decision is not valid, this is because there is no regulation between the old law and the new law. This research used a normative juridical approach which was carried out through analysis obtained from library materials linked to statutory regulations and the concept of legal experts as the basis for research. The result of this research was that harmonization emphasized more on equating perceptions of the implied meaning without making editorial changes. Reconstruction of norms, including improving old laws or making new laws by changing the editorial staff of articles that still contain contradictions.